Combined Anterior Cruciate Ligament Reconstruction Revision and Double-Bundle Medial Collateral Ligament and Posterior Oblique Ligament Reconstruction - Arnault Valette MD; Dany Mouarbes MD; Vincent Marot MD; Etienne Cavaignac MD, PhD (SAGE Publishing, 2021)
Background: Nonsurgical treatment of concomitant medial collateral ligament (MCL) in the setting of anterior cruciate ligament reconstruction (ACLR) increases the risk of graft failure. Few published cases of medial complex reconstruction combined with ACLR with no clear consensus on the optimal technique to treat these complex injuries. Indications: A female patient aged 41 years, with failure of ACLR in 2009 and 2 revisions in 2013 and 2014, associated with concomitant nontreated MCL and posterior oblique ligament (POL) injury. Physical examination showed valgus test laxity grade III at 30° of knee flexion and at full extension, with Lachman and pivot-shift test grade III. Imaging showed normal long-leg standing axis with 10° posterior tibial slope on radiograph, and associated MCL and POL injury on magnetic resonance imaging. Technique Description: ACLR and anterolateral tenodesis using the fascia lata leaving its distal insertion on the Gerdy tubercle, with double-stranded contralateral gracilis, was completed. A new femoral tunnel was made from outside to inside, with preservation of the previous tibial tunnel. The transplant was fixed with 2 interference screws. Second, the contralateral semitendinous autograft was used for MCL and POL reconstruction. A single strand of the graft was used for femoral fixation created on femoral epicondyle to cover MCL and POL origins, and double strands were used for distal fixation of MCL at the level of hamstring insertion and POL at the posteromedial corner of medial tibial plateau. The graft was secured with 3 interference screws at 30 knee flexion for MCL and full extension for POL. Results: The results include favorable functional and clinical outcome with improvement in the anteroposterior and rotatory knee stability at mid-term follow-up. Lateral extra-articular tenodesis in supplementing ACLR controls internal tibial rotatory knee stability. Double-bundle reconstruction of MCL and POL improved both valgus and anteromedial rotatory instability by restraining external rotation. Discussion/Conclusion: Surgeons should consider the need for surgical treatment of concomitant MCL injury to prevent chronic valgus laxity and increased strain on the anterior cruciate ligament (ACL) graft, potentially increasing the risk of ACLR revision. Our described technique offers a safe method for ACLR and lateral tenodesis with an advantage to avoid tunnel convergence, and medial stabilization to restore native valgus and rotatory stability and prevent increased stress on ACL graft.